A multicenter pilot survey to clarify the clinical features of patients with acute‐on‐chronic liver failure in Japan. Issue 4 (2nd March 2018) - Nakayama, Nobuaki; Uemura, Hayato; Uchida, Yoshihito; Tomiya, Tomoaki; Ido, Akio; Inoue, Kazuaki; Genda, Takuya; Takikawa, Yasuhiro; Sakaida, Isao; Terai, Shuji; Yokosuka, Osamu; Shimizu, Masahito; et al.
Abstract : Aim: To establish diagnostic criteria for acute‐on‐chronic liver failure (ACLF) in Japan, a multicenter pilot survey was carried out to examine the usefulness of overseas criteria in patients with chronic liver diseases manifesting acute decompensation. Methods: Patients fulfilling the Asian‐Pacific Association for the Study of the Liver (APASL), European Association for the Study of the Liver (EASL), or Chinese Medical Association (CMA) criteria for decompensation were enrolled from eight institutions in Japan, and the clinical features were evaluated. Results: Among 112 patients, 109 patients (97.3%) fulfilled the APASL criteria for decompensation; 7 patients were excluded because the decompensation had been provoked by gastrointestinal bleeding. Consequently, 102 patients (91.1%) were diagnosed as having ACLF according to the APASL definition. Among the patients who fulfilled the APASL criteria for decompensation, the etiologies of the underlying liver diseases were alcohol abuse in 59 cases (54.1%) and hepatitis B or hepatitis C virus infection in 24 (22.0%). The acute insults were alcohol abuse in 50 (45.9%), bacterial infection in 26 (23.9%), and exacerbation of underlying liver disease in 14 (12.8%). Fifty‐four patients (49.5%) satisfied the CMA criteria, but the survival rates were similar between patients who did and those who did not meet the criteria. When 84 patients with underlying cirrhosis were classified according to the EASL–Chronic Liver Failure (Clif) Consortium criteria, the survival rates differed according to grade: 67.6% (23/34) for patients without ACLF, and 41.2% (14/34) and 18.8% (3/16) for those with grade 1/2 and grade 3 ACLF, respectively. Conclusion: The APASL definition was suitable for screening Japanese patients with ACLF, including those whose conditions were triggered by gastrointestinal bleeding, and the EASL‐Clif Consortium criteria were useful for predicting outcome.